210Po bioaccumulation and trophic transfer in marine food chains in the northern Arabian Gulf. (August 2017) - Uddin, S.; Fowler, S.W.; Behbehani, M.; Metian, M.
Abstract: The tendency of 210 Po to concentrate in body tissue poses a serious concern of radiological safety. This study compiles available information and presents recent 210 Po data for the marine food web in the northern Gulf waters. Since 210 Po is concentrated in marine biota, a large number of samples of various marine organisms covering several trophic levels, from microalgae to sharks, were analyzed. 210 Po was found to be highly concentrated in several marine species with the highest 210 Po concentrations found in yellowfin tuna, i.e. 37.3–44.9, 451–548, and 1511–1693 Bq kg −1 wwt in muscle, digestive system and liver, respectively. In most dissected fish samples, 210 Po showed increasing concentrations in the following order: edible tissue, gills, digestive system, liver and fecal matter. Fish feces had 210 Po concentrations several orders of magnitude higher than that in seawater, fish muscle, and the fishes' ingested food. The high 210 Po concentration in fish fecal matter suggests that the bulk of 210 Po content in fish is eventually excreted back into the environment as fecal pellets. In most fish high concentrations were noted in liver, with the highest 210 Po concentration recorded in yellowfin tuna liver. Moreover, 210 Po concentration in the soft tissue of tunicate and bryozoan samples were 872–1012 and 402–527 Bq kg −1 wwt, respectively, far higher than that in fish muscle (0.04–44.9 Bq kg −1 wwt). It was observed that the maximum 210 Po concentration in edible fish tissue among the fish in trophic level 2 was an order of magnitude lower than those in trophic level 3 and two orders of magnitude lower compared to fish in trophic level 4. The highest concentrations in the muscle tissue were observed in the following order: tunicate > bryozoan > mollusc > crustacean > algae > fish. Among all the biota analyzed, the highest overall concentration of 210 Po was noted in yellowfin tuna ( Thunnus albacores ) indicating a potential biomagnification of 210 Po in this particular top predator species. In general, 210 Po concentrations found in the commercially important fish from Kuwaiti waters were comparable to levels that have been reported for similar fish species from several other marine areas worldwide. Highlights: This paper describes trophic transfer of 210 Po in the marine food web. Provides a improved understanding of 210 Po distribution in fish tissues. Establishes a relationship between 210 Po body concentrations and dietary uptake of fish.